Epidermal keratinocytes sense dsRNA via the NLRP3 inflammasome, mediating interleukin (IL)‐1β and IL‐18 release. Issue 10 (12th May 2017) - Dai, Xiuju; Tohyama, Mikiko; Murakami, Masamoto; Sayama, Koji
Abstract: Skin epidermis, in addition to its barrier function, is able to actively sense harmful pathogens using pattern recognition receptors. In immune cells, the nucleotide‐binding oligomerization domain, leucine‐rich repeat and pyrin domain containing 3 (NLRP3) inflammasome can mediate innate immunity against viral infection via a mechanism involving viral dsRNA recognition. Epidermal keratinocytes express NLRP3 inflammasome, which can sense contact sensitizers and mite allergens, leading to pro‐interleukin (IL)‐1β and pro‐IL‐18 cleavage into their active forms. Skin often faces viral infection. However, it is unknown whether viral dsRNA can be detected by the keratinocyte NLRP3 inflammasome. We transfected polyinosinic:polycytidylic acid (poly I:C), a synthetic viral dsRNA analogue, into cultured primary human keratinocytes at the aid of Lipofectamine 2000, and found that transfected poly I:C activated caspase‐1 and induced caspase‐1‐dependent release of IL‐1β and IL‐18, which were suppressed on transfection with NLRP3 siRNA. The activation of keratinocyte NLRP3 inflammasome by transfected poly I:C was dependent on dsRNA‐induced protein kinase (PKR) activation, and priming with type I interferons upregulated NLRP3 inflammasome activation through promoting PKR activation in poly I:C‐transfected keratinocytes. In conclusion, the NLRP3 inflammasome can act as a sensor of dsRNA in epidermal keratinocytes, which may be important in both skin innate immune defense against viral infection and skin inflammation.